Prevention and Detection of Attacks in MANET Using Hybrid Approach - Mr. Mayur Agrawa, Ms.Apurva Kulkarni, Mr.Prashant Rewagad (International Journal of Scientific Research and Management (IJSRM), 2015)
These MANET Stands for Mobile Ad-hoc network is an autonomous system of mobile routers and its associated hosts connected by wireless links. Because MANETS are mobile, they use wireless connections to connect to various networks Mobile Ad-hoc Network are formed dynamically by an Autonomous system of mobile nodes that are connected via wireless links. Nodes in MANET Communicate directly with each other when they are in same communication range otherwise they rely on their neighbors to send messages.MANET is a unique application. MANET is prone to various types of attacks due to its increased use. So Todays urgent need is to develop efficient intrusion-detection system to protect MANET from malicious attacks.This paper focuses on Enhanced Adaptive Acknowledgment (EAACK) which is an IDS Specially designed for MANET which will detect malicious nodes very efficiently and in addition to that EAACK can be extended further by adopting hybrid encryption as a preventive measure which will enhance security of messages in MANET.